Study of Compressive Strength of Concrete with Coal Power Plant Fly Ash as Partial Replacement of Cement and Fine Aggregate - FAREED AHMED MEMON; NAFEES AHMED MEMON; RIZWAN ALI MEMON (Mehran University Research Journal of Engineering and Technology, 2010)
This research study comprises of concrete cubes made with Ordinary Portland Cement and with different configurations of fly ash by replacing cement and fine aggregate. To achieve the aim of this study, total 81 concrete cubes were cast. Among 81 cubes, 9 cubes were made with normal concrete, 36 cubes were made by replacing 25%, 50%, 75% and 100% of fine aggregate with fly ash and 36 cubes were made by replacing 10%, 25%, 50%, and 75% of cement with fly ash. The cubes were 6\" x 6\" in cross-section, and the mix design was aimed for 5000 psi. After proper curing of all 81 cubes, they were tested at 3, 7 and 28 days curing age. The cubes were tested in Forney Universal Testing Machine. By analyzing the test results of all the concrete cubes, the following main findings have been drawn. The compressive strength of concrete cubes made by replacing 100 % fine aggregate by fly ash was higher than the concrete cubes made with Ordinary Portland Cement at all 3, 7 and 28 days curing ages. On the other hand, the compressive strength of concrete cubes made by replacing 10 % and 25 % cement by fly ash was slightly lower than the concrete cubes made with Ordinary Portland Cement at all curing ages, whereas, the compressive strength of concrete cubes made by replacing 50 % and 75 % of cement by fly ash were quite lower than the concrete cubes made with Ordinary Portland Cement at all curing ages.